Influence of the implantation of a dynamic inter-spinous stabilizer for a functioning condition and pain ailments of patients with the discopathy of lumbar spine - Sylwia Spandel; Ewelina Bąk; Leszek Spandel; Sylwia Krzemińska (Kazimierz Wielki University, 2017)
Introduction   The lumbar disc herniation is a common health problem of modern society. In many cases it requires operational intervention.   Objective The aim of this paper is to evaluate the effect of DIAM TM interactions on intraoperative stabilizers in functional and pain levels in patients with lumbar spine dysopatia.   Material and methods   The study included 52 patients who underwent spinal disc herniation. Oswestry (ODI), Visual Analog Scale (VAS), and the author's questionnaire were used to test the effect of the procedure.   Results   In the study group, the mean ODI score before surgery was 20.81 (± 5.99), and after 6 months after surgery the rate was significantly lower than 12.94 (± 5.42). Average intensity of pain acc. For VAS before and after surgery respectively 3.15 (± 1.28) and 1.58 (± 1.14).   Conclusions   Implementing an internal DIAM TM in a short period of time leads to a significant reduction in pain and improved patient functioning.